The Policy Implementation Analysis of Ministry of Education, Culture, Research and Technology Regarding Technical Guidelines for School Operational Costs to Increasing The Quality of Learning Activities for Junior High School Students in Jakarta - Debby Yulianty Chusnady; Yulianto Yulianto (Journal on Education, 2023)
This study aims to analyze and evaluate the implementation of the policy of the Minister of Education and Culture Number 6 of 2021 concerning Technical Guidelines for School Operational Costs (BOS) as an effort to increase learning activities for students. Analyze and evaluate the factors that hinder the implementation of Minister of Education and Culture Regulation Number 6 of 2021 concerning Technical Guidelines for School Operational Costs (BOS) as an effort to increase learning activities for students. Analyze and evaluate solutions to overcome obstacles to policy implementation Regulation of the Minister of Education and Culture Number 6 of 2021 concerning Technical Guidelines for School Operational Costs (BOS) as an effort to increase learning activities for students. This study used a qualitative method using purposive sampling. The results of the school principal's research have been materialized and proven to be well applicable in schools for the use and management of BOS grants. There are characteristics and communication between organizations.